Macro News, Riskfree Rates, and the Intermediary - Albert J. Menkveld; Asani Sarkar; Michel van der Wel (Tinbergen Institute, 2007)
Signed customer order flow correlates with permanent price changes in equity and nonequity markets. We exploit macro news events in the 30Y treasury futures market to identify causality from customer flow to riskfree rates. We remove the positive feedback trading part and establish that, in the 15 minutes subsequent to the news, intermediaries rely on customer orders to determine a substantial part of the announcement's effect on riskfree rates, i.e. one-third relative to the instantaneous effect. They appear to benefit from privately observing informed customers, as, in the cross-section, their own-account trade profitability correlates with access to customer flow, controlling for volatility, competition, and the macro ``surprise''.
Keywords: G14; E44; 330; discount rate; macroeconomic announcements; customer order flow; intermediary; treasury futures; Ankündigungseffekt; Wertpapierhandel; Derivat; Börsenmakler